Gacha games: the unregulated mobile casino - See, Darryl Mingkun (Nanyang Technological University, 2025)
In today’s culture, the unseen threat of gambling has pervaded the games that many utilise to pass time. Yet for such a prevalent threat, the possible problems it brings has remained largely ignored by most governments. In this essay, I will question the ethical issues of gambling hidden within games, especially in the context of vulnerable groups within society. This essay aims at understanding the harm that unregulated gambling within video games causes vulnerable groups (i.e., children) due to the predatory nature of such addictive services and aims to unpack the factors that cause vulnerable groups to be more susceptible to the addiction of gambling. In the end, I conclude that the harm caused by gambling is largely attributable to the addiction caused by such gambling and that this epidemic could possibly be combated through government intervention and imparting more knowledge to vulnerable groups.